Studi tentang Karakteristik Light Dependent Resistor - Marcelita Tjuana; Heindrich Taunaumang; Jimmy Lolowang (Jurnal FisTa : Fisika dan Terapannya, 2023)
The purpose of the study was to analyze the relationship between the light intensity received by the LDR and the resistance it produces. In this study, the LDR components are arranged in series and parallel. Then the measurements are placed in 4 different light condition with the light source used, namely 5 watt lamps, 10 watt lamps, 15 watt lamps and conditions before the lights are turned on (dark). The tool used to measure the intensity of light is a digital lux meter and to measure the resistance value using a digital multimeter. The results of this study indicate that the greater the light intensity received by the LDR, the smaller the resulting resistance is 2 KΩ for the series circuit and 55 Ω for the parallel circuit at a light intensity of 7242 lux. Conversely, the smaller the intensity of the light received by the LDR, the greater the resistance it produces, namely when in dark conditions the resistance produced by the LDR in series is 994 KΩ and in the parallel LDR the resulting resistance reaches 1194 Ω. The resistance of a series LDR circuit is greater than the resistance of a parallel LDR circuit for each intensity of light it receives.